2020
DOI: 10.18415/ijmmu.v7i2.1416
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Online Learning

Abstract: The development of technology has indirectly influenced the world of education. These influences include online learning. This study aims to determine the effect of student perceptions on the application of online learning. This research is a descriptive verification study with an ex post facto and survey approach. The results of this study reveal that although there were some students who were less satisfied with online learning, the majority of students already knew that online learning had a good perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Multimedia combines various types of digital media (such as text, images, sound, and video) into integrated multi-sensory interactive applications or presentations to convey messages or information to audiences (McEwan & Caincross Sandra, 2004;Neo Ken & Neo, 2004). The use of multimedia in learning can improve the competence of vocational students (Maskun, Rusman, Suroto, & Rahmawati., 2020), especially in enhancing the competence of business presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Multimedia combines various types of digital media (such as text, images, sound, and video) into integrated multi-sensory interactive applications or presentations to convey messages or information to audiences (McEwan & Caincross Sandra, 2004;Neo Ken & Neo, 2004). The use of multimedia in learning can improve the competence of vocational students (Maskun, Rusman, Suroto, & Rahmawati., 2020), especially in enhancing the competence of business presentations.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to create an authentic learning experience environment is one of the critical factors in online teaching and learning (Serfozo et at., 2022). In addition, previous studies found that easy-to-use and easy-to-learn tools or learning platforms increase learners' motivation and engagement (Maskun et at., 2020;Domina et at., 2021). This research uses Gather Town and Google Forms to design an online educational game that builds communication and responsiveness in the service industry; allowing learners to have a realistic simulated spatial environment and use their familiar online forms to learn reduces their learning anxiety and increases their learning effectiveness and engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Online learning is the only option that requires students to use technology in distance learning (Geng & Masanori, 2020;Kadeeva et al, 2020;Mon, 2020). Online learning is a revolution current educational technology (Maskar & Wulantina, 2019;Rusman & Rahmawati, 2020;Yustika et al, 2019). But online learning has been a long time developed (Nguyen, 2015;Teodorescu, 2015;Ventura, 2015).…”
Section: Introductionmentioning
confidence: 99%